Creación de un modelo de medición de competencias para aspirantes a especialización y maestría en desarrollo y gerencia integral de proyectos en la Escuela Colombiana de ingeniería (2018)
This degree work presents the creation of a measurement model of competencies which is useful for decision makers of companies or projects in the selection of candidates for project management. The creation of this model is based on the opinion of experts who have been selected taken into consideration a five years experience in project management. The information given by the experts is used with the purpose of obtaining the necessary competencies for a project manager. This information is compared by using a tool named "Competency Gaps", which goal is to identify the coincidences between the experts' and the pilot group's competencies. The results obtained through the "Competency Gaps" are analyzed and described in this article with the purpose of suggesting a competency measurement model for potential project manager candidates. The methodology used is based on a oriented interview with the purpose of knowing the key competencies for a project manager.